Collective Labour Conflicts in Companies and Public Institutions: Some Prospects - Raluca DIMITRIU (Transylvanian Review of Administrative Sciences, 2011)
Participation of the employees and of the public servants in collective labor conflicts constitutes a significant chapter regarding the concrete way in which the Romanian legislator implements the concept of flexicurity and re-defines labor relations. Indeed, the entire Romanian legislation on labor relations and dispute resolution has been tremendously changed in May 2011, and the impact of these changes is about to be very intense. The new law on collective labor conflicts, currently at crossroads, is rather susceptible to discourage the initiation of such conflicts and even to limit the freedom of strike. The legislator adopted a unified regulation, applicable to both employees and public servants; as such individuals who work under an employment contract are governed by the same dispute resolution norms as those individuals who perform their professional activity under an administrative act. Beyond the theoretical aspects that the new view of the Romanian laws on the labor conflict resolution raises, there are many direct, practical consequences, as well as difficulties that courts face since the entering into force of the new legislation. This study aims to analyze some of these practical consequences.